Structure and function of Full-length Tau - Laura Vallés-Saiz; Indalo Domene-Serrano; Angel J. Picher; Mar Pérez; Vega García-Escudero; Félix Hernández; Jesús Avila (PLoS ONE, 2025)
Tau protein, encoded by the MAPT gene, is a microtubule-associated protein involved in the regulation of microtubule stability in neurons, contributing to cell shape maintenance and intracellular transport, among other functions. Tau is not found as a unique isoform; instead, different Tau isoforms of varying sizes are present in the brain, but a Full-length Tau isoform (Full Tau) containing all 16 exons has never been previously identified. This study has explored the structure and function of the Full Tau isoform, which includes all exons of the MAPT gene. To achieve this, we expressed the Full Tau isoform in bacteria, alongside the Tau 4R2N isoform as a control, and tested its microtubule-binding capacity, self-aggregation propensity, and effects on cultured cells regarding cell proliferation and cell death. Our results indicated several differences between the Full Tau and Tau 4R2N isoforms, suggesting distinct roles in cellular dynamics. To explain these differences, we suggest the role of exon 8, which is present in the Full Tau isoform but absent in Tau 4R2N.